PELATIHAN STORYTELLING DAN PERMAINAN BAHASA INTERAKTIF SEBAGAI STRATEGI LITERASI KREATIF UNTUK ANAK DI RA NURUL HUDA - Rofi'ah, Ulya Ainur; Oktaviana, Widya Fajar; Mundzir, Moh.; Muslimin, Muslimin; Ngainin, Nurul; Hidayati, Ninik; Fauzi, M. (CV. Kalimasada Group, 2025)
This study employs a qualitative approach using action research methodology to optimize the language skills of children aged 4-5 years through a storytelling training program and interactive language games as a creative literacy strategy at RA Nurul Huda Semarang. The research subjects consisted of 23 students aged 4-5 years, along with teachers and parents who were directly involved in the program implementation. The findings indicate that storytelling and interactive language games significantly enhance children's language skills, including vocabulary mastery, fluency in speaking, comprehension of sentence structures, and confidence in expressing ideas verbally. This method also creates a more enjoyable learning environment and fosters the development of children's creativity and imagination in communication. Furthermore, the training program positively impacts teachers’ teaching strategies, making them more interactive, and increases parental involvement in supporting creative literacy at home. Thus, this study confirms that the storytelling approach and interactive language games are effective strategies for improving early childhood language skills. This program can be more widely implemented as a strategic effort to build a strong literacy foundation, fostering a generation that is more communicative, creative, and confident in using language as a tool for thinking and interacting.